2009
DOI: 10.1245/s10434-009-0403-y
|View full text |Cite
|
Sign up to set email alerts
|

Additional Tracer Injection to Improve the Technical Success Rate of Lymphoscintigraphy for Sentinel Node Biopsy in Breast Cancer

Abstract: Background. Sentinel node (SN) biopsy has become the standard of care in the treatment of breast cancer. The aim of this study is to determine the value of additional tracer injection to increase the technical success rate of the SN procedure and to identify factors that influence the ability to visualize hotspots. Methods. From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…These investigators hypothesized that nodal metastases might completely obstruct the lymph flow, preventing the radiotracer from accumulating in the SLN, and thus leading to nonvisualization on lymphoscintigraphy. The routine use of preoperative ultrasonography of the axilla in combination with fine‐needle aspiration cytology (US/FNAC) of regional lymph nodes was not reported in the studies that found extensive nodal metastatic involvement in patients with nonvisualization on preoperative imaging . Kramer et al demonstrated that preoperative US/FNAC has an adequate accuracy of 89.8% to detect three or more positive lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…These investigators hypothesized that nodal metastases might completely obstruct the lymph flow, preventing the radiotracer from accumulating in the SLN, and thus leading to nonvisualization on lymphoscintigraphy. The routine use of preoperative ultrasonography of the axilla in combination with fine‐needle aspiration cytology (US/FNAC) of regional lymph nodes was not reported in the studies that found extensive nodal metastatic involvement in patients with nonvisualization on preoperative imaging . Kramer et al demonstrated that preoperative US/FNAC has an adequate accuracy of 89.8% to detect three or more positive lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…In primary breast cancer, the injection of a larger amount of 99m Tc appears to lead to a higher identification rate, which is comparable to our findings in the recurrent breast cancer setting. [10][11][12] In the current European Association of Nuclear Medicine and Society of Nuclear Medicine and Molecular Imaging Guideline on lymphoscintigraphy, a dose of 5 to 30 MBq is considered sufficient in a 1-day LM protocol. For a 2-day protocol in primary breast cancer, injection of 150 MBq 99m Tc is advised.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Also, the injection site and the quadrant of the breast in which the tumor is located have been shown to influence the identification and the amount of extra-axillary SN visualization. 10,[13][14][15] Dual mapping with technetium-99m ( 99m Tc) and blue dye improves the SN visualization.…”
mentioning
confidence: 99%
“…This may result from a number of reasons, including technical issues such as a suboptimal tracer particle size or tracer injection technique 5, non‐visualization is known to be more common after intra‐parenchymal tracer injections than superficial techniques 5. Also patient‐related features such as old age 5–10, large body mass index 5–10, and previous breast surgery 11, 12, influence the visualization. Importantly, presence of cancerous tumor growth in the axilla might obstruct the normal lymphatic flow, increase the risk of node non‐visualization and lead to a false‐negative SNB 13–17.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐visualization in lymphoscintigraphy is associated with an increased intra‐operative failure rate of the SNB, thus leading to ALND 10, 18, 19. Therefore, a second radiocolloid tracer injection has been advocated to improve identification of the sentinel nodes and to decrease SNB failure rate 6, 20. We have shown in our previous report, with partly the same patient population and equal SNB methods as the present study, that in case of axillary non‐visualization in lymphoscintigraphy a second radiotracer injection significantly increases the axillary SN identification rate and the SNB success rate, thus decreasing the need for ALND of healthy axilla 19.…”
Section: Introductionmentioning
confidence: 99%